PREPARATION OF STAR-SHAPED POLYLACTIDE WITH PENTAERYTHRITOL AND STANNOUS OCTOATE - KIM, SH; HAN, YK; AHN, KD; KIM, YH; CHANG, T (HUTHIG & WEPF VERLAG, 1993)
The ring-opening polymerization of L-lactide with stannous octoate was investigated in the presence of pentaerythritol. By this way it was possible to prepare higher molecular weight star-shaped poly(L-lactide)s compared with the linear ones obtained by stannous octoate only. The weight-average molecular weights of linear and star poly(L-lactide)s were measured by light scattering analysis from hexafluoro-2-propanol solution, and the respective Mark-Houwink equations were derived. The second virial coefficient and the intrinsic viscosity of the star polymers were lower than those of the linear ones, which confirms the star-shaped architecture.